2017
DOI: 10.1007/s10921-016-0389-x
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Influence of Plastic Deformation Induced Residual Stress on the Barkhausen Effect Signal in Martensitic Steels

Abstract: The paper presents the results of investigation of the influence of plastic deformation on the magnetic properties of martensitic steel (P91 grade). The properties of the hysteresis loops as well as of the Barkhausen effect (BE) signal are analysed for both tensile and compressive loading up to ε = 10% of plastic deformation. The choice of the steel and of the deformation range is unique, since for such combination one can expect high residual stresses (both compressive and tensile) in the material that does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…As it turned out the obtained dependence of the filtered MAE signal intensity on the deformation level is very similar, yet due the better resolution, one can observe that the changes due to the tensile deformation are in fact non monotonous there is a local maximum for ε = 1.6%. One could suspect that to be an erroneous result, yet analogous maximum was observed for the BN signal intensity [4]. Probably it is due to creation of a dislocation cell structure for that range of deformation.…”
Section: Resultsmentioning
confidence: 77%
“…As it turned out the obtained dependence of the filtered MAE signal intensity on the deformation level is very similar, yet due the better resolution, one can observe that the changes due to the tensile deformation are in fact non monotonous there is a local maximum for ε = 1.6%. One could suspect that to be an erroneous result, yet analogous maximum was observed for the BN signal intensity [4]. Probably it is due to creation of a dislocation cell structure for that range of deformation.…”
Section: Resultsmentioning
confidence: 77%
“…It has been shown that they can be characterized by analysing the characteristics of the magnetic noise [1,2], caused by the dislocations in the microstructure in the examined ferromagnetic material. The information provided by these characteristics enables differentiated processing of the information used to evaluate the multiparameter analysis of the nitriding mode and other types of processing of each individual input parameter [3,4,5]. This is possible thanks to the property of ferromagnetic bodies discovered by Barkhausen, whose magnetization under the action of an external magnetic field is accompanied by numerous jumps in magnetization.…”
Section: Introductionmentioning
confidence: 99%